Edukasi Kreativitas Kepedulian Sosial Melalui Program Keterampilan Prakarya dan Baksos di Panti Jompo Karya Kasih - Agus Sriyanto; Nora Adira Brabo; Ifan Haryanto; Iis Torisa Utami; Fathur Ridwan; Kim Mi (Jurnal Kemitraan Masyarakat, 2026)
The "Educating Social Awareness Creativity Through Craft Skills and Social Service Programs at the Karya Kasih Nursing Home" activity is part of a community service program implemented by lecturers and students at Budi Luhur University. This activity aims to provide moral and social support to the elderly through educational and social activities. The program includes craft skills training, providing basic food assistance, and entertainment activities involving lecturers, students, and nursing home residents. The activity implementation method uses a participatory approach, where students interact directly with the elderly for two weeks. This approach is designed to create positive social relationships, increase emotional engagement, and provide contextual learning experiences for students. The results of the activity indicate that this program has a positive impact on the elderly, particularly in increasing happiness, social interaction, and creative activities. In addition, this activity also contributes to the development of students' soft skills, especially in terms of social empathy, intergenerational communication, and social awareness. Thus, this community service program not only provides benefits for the elderly as recipients of the program